Use of the Integra skin regeneration system in an intraoral mandibular defect in osteoradionecrosis. Issue 9 (September 2016) - Beech, A.; Farrier, J.
Abstract: The objective was to trial the use of the Integra skin regeneration system intraorally to promote healing of an intraoral defect in osteoradionecrosis (ORN), thereby avoiding the necessity for mucosal flaps, free flaps, or skin grafts. A 54-year-old male patient presented with a pathological mandibular fracture at the angle, related to previous radiotherapy for tonsillar carcinoma, after the development of ORN. The fracture site was debrided and fixed with a reconstruction plate and the intraoral defect was dressed with the Integra two-layer system and an overlying pack. Three weeks later, the pack and silicone layer of the regeneration system were removed, showing early granulation over the previously exposed bone. At 8 weeks postoperative, the defect had healed completely with no need for further reconstruction. Using the method described, excellent healing was seen with the Integra skin regeneration system. A new use for the Integra skin regeneration system has been identified in the authors' unit. This method is minimally invasive and resulted in good healing in the case presented. The need for further reconstruction with associated increased patient morbidity was avoided in this case.